Evaluation of treatment outcome in gingival hyperpigmentation with scalpel Vis-a-Vis Laser: A split-mouth study - Oliver Jacob; Manab Kosala; Mohinder Panwar (Wolters Kluwer Medknow Publications, 2021)
Context: Melanin pigmentation of the gingiva is a physiological process that occurs in all ethnicities. Many treatment modalities are available to treat gingival hyperpigmentation. These are based on the principle of complete removal of the epithelial layer along with a part of subepithelial connective tissue which is then permitted to heal by secondary intention. Aim: This study aims to compare the treatment outcome of laser and its effectiveness in the management of gingival hyperpigmentation over scalpel. Design: A split-mouth study. Methods: Twenty young patients, between the ages of 18-35 with no systemic comorbidities with concerns regarding of dark-colored gums were selected for the study. A split-mouth study involving treatment of melanin pigmentation using scalpel abrasion on one side (left side upper and lower jaws) and Diode laser (980 nm) on other side (right side upper and lower jaws) was carried out. Observations regarding time taken, amount of bleeding during procedure, postoperative pain, healing of wound, and recurrence were made. Statistical Analysis: Data were analyzed using SPSS version 21.0 for Microsoft Windows. Results: Pain and healing were comparable in both the groups, though intraoperative time consumed and bleeding was significantly lower for laser group. Recurrence also was significantly lower on the laser group. Conclusion: Diode lasers can give better results in the management of gingival pigmentation compared to conventional scalpel abrasion technique.